Introduction of Fluorine Into spiro[fluorene‐9, 9′‐xanthene]‐Based Hole Transport Material to Obtain Sensitive‐Dopant‐Free, High Efficient and Stable Perovskite Solar Cells. Issue 4 (7th February 2019) - Guo, Kunpeng; Wu, Min; Yang, Shaomin; Wang, Zongtao; Li, Jie; Liang, Xiaozhong; Zhang, Fang; Liu, Zhike; Wang, Zhongqiang
Abstract : Despite the substantial development of efficient hole transporting materials (HTMs) for high‐performance perovskite solar cells (PSCs), optimization of the HTMs to sensitive‐dopant‐free HTMs for high efficient PSCs with prominent stability have rarely been reported. Herein, a low‐cost fluorinated spiro[fluorene‐9, 9′‐xanthene] based HTM termed2 m F‐X59 is designed and synthesized. In comparison with its reported nonfluorinated counterpart X59, 2 m F‐X59 shows lowered highest occupied molecular orbital (HOMO) level, improved hole mobility, and hydrophobicity. Aided by 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane (F4TCNQ) to further lower the HOMO level of2 m F‐X59 and improve its hole transfer, the optimized2 m F‐X59 based PSCs show a maximum power conversion efficiency (PCE) of 18.13% without the use of any sensitive‐dopants (e.g., lithium salt/4‐tert‐butylpyridine), which is comparable to the Spiro‐OMeTAD based PSCs (18.22%) with sensitive dopants. More importantly, the sensitive‐dopant‐free2 m F‐X59 based PSCs maintain 95% of their initial performance for more than 500 h under air exposure, showing much better long‐term stability than control PSCs based on Spiro‐OMeTAD with sensitive dopanst. This is the first case that a sensitive‐dopant‐free HTM is demonstrated in PSCs with a high PCE (>18%) and good stability by optimizing the literature HTM. This work could pave a new way to develop low‐cost sensitive‐dopant‐free HTMs for highly efficient and stable PSCs for practical applications. Abstract : A fluorinated spiro[fluorene‐9, 9′‐xanthene] based hole transport material (HTM), 2mF‐X59, is designed and synthesized within two steps for sensitive‐dopant‐free, high efficient, and stable perovskite solar cells (PSCs). 2 m F‐X59 shows the lowered HOMO level, improved hole mobility and hydrophobicity, compared to its nonfluorinated counterpart X59. Without the use of any sensitive‐dopants, the optimized 2 m F‐X59‐based PSCs exhibit a power conversion efficiency up to 18.13% with impressive long‐term stability.